PENGARUH INFLASI, KURS, PENANAMAN MODAL ASING(PMA) TERHADAP EKPOR NON MIGAS DI INDONESIA - Muhamad Fajar Septiawan (2022)
This research aims to determine the effect of inflation, exchange rates, and foreign investment (PMA) on non-oil and gas exports in Indonesia in 1991 - 2020. The type of data in this research uses secondary data in the form of time (time series) and is data for the annual period 1991 - 2020 , which was processed using quantitative analysis techniques with the Ordinary Least Square (OLS) method. The results of multiple linear regression analysis show that (1) there is no significant effect on inflation on non-oil and gas exports (2) Exchange rates (exchange rates) have a significant effect on non-oil and gas exports (3) Foreign Investment has no significant effect but is in line with non-oil and gas exports.